PEMBENTUKAN KARAKTER RELIGIUS SANTRI DALAM UPAYA MENANGKAL FAHAM RADIKALISME DI PONDOK PESANTREN DAARUN NAJAH SUKORAME LAMONGAN - samsul ma'arif (Universitas KH. A. Wahab Hasbullah, 2020)
This research aims to describe and analyze about the establishment of the character Santri to ward off the radicalism in the boarding school Daarun Najah Sukorame Lamongan. The background of this research is the publication of an event or a provocative notion of Islamic education, especially education in Pesantren which is considered to be exposed to radicalism with evidence of the many occurrences of suicide bombing or Terrorism which is on behalf of the religion of Islam, so that the things that have a relationship with the religion of Islam to be feared in some circles society. Whereas education is essentially forming human beings who can humanize humans to be the people of Kamil. Educational objectives to improve human creed. One of the efforts of the moral establishment is through coaching and planting the value of morality that exist in the pesantren. Based on the background researchers tried to research the education in the foundation of boarding school Daarun Najah Ahmad Yani sukorame Lamongan by making a problem formula, 1. How is the efforts of boarding school Daarun Najah in the formation of religious students to ward off radicalism? 2. What are the supporting factors and barriers to the efforts of boarding school Daarun Najah in the formation of religious students to ward off radicalism? The results showed that the establishment of religious character students in an attempt to ward off radicalism in the boarding school Daarun Najah Sukorame Lamongan, is very good by embedding religious characters such as Ihlas, Istiqomah and Tawadu ' and embed the national character and love the homeland by following the ceremonies of the national Day, and the introduction of the history of the national heroes, supporting factors of the formation of students in the cottage is the support of the various elements that exist In huts from caregivers, ustadz and caretakers. And elicit a clear ustadz background as well as a conducive cottage environment, while its inhibitation factor is Western ideology and culture that is not in accordance with Islamic and Javanese culture, open breadth of social media, and surrounding environment Unconducive huts.